Is D2 Lymphadenectomy in Gastrectomy Safe with Regard to the Skill of the Operator? - Moriwaki, Yoshihiro; Kobayashi, Syunsuke; Kunisaki, Chikara; Harada, Hirofumi; Imai, Sinsuke; Kido, Yasuhiro; Kasaoka, Chitaka (Digestive surgery, 2001)
Background/Aims: D2 gastrectomy has been regarded as an inconvenient procedure with high morbidity and no survival benefit in the West. Recent western studies, however, especially from specialist centers, have shown a survival benefit and the safety of D2 gastrectomy. The aim of this study is to clarify the safety of D2 gastrectomy (defined by the Japanese Research Society for the Study of Gastric Cancer), even if carried out by a junior surgeon, and to show that it is not a particularly difficult or special procedure. Methods: Patients who underwent a typical distal gastrectomy (DG) with D2 resection (n = 344) and total gastrectomy (TG) with D2 resection (n = 111) were analyzed. The subjects were divided into 3 groups according to the postgraduate year of the operator (group I = the surgeon’s postgraduate experience was less than 5 years; group II = surgeons with more than 5 years and less than 10 years postgraduate experience; group III = surgeons with more than 10 years postgraduate experience). The rate of postoperative complications and the 5-year survival rate were compared among the 3 groups. Results: The overall operative mortality rate, hospital death rate and the overall rate of postoperative complications were 1.2, 2.0 and 10.2% in DG patients, and 14.4, 0 and 1.8% in TG patients, respectively. There was no significant difference in the operative blood loss, the rate of operative mortality, hospital death rate and postoperative complications among the 3 groups. There was no significant difference in the 5-year survival rate among the 3 groups in each stage. Conclusion: The postoperative mortality rate, morbidity rate and 5-year survival rate after a typical D2 gastrectomy were independent of the experience of the operator. It is considered to be a safe and useful procedure in view of the rate of postoperative complications and the long-term survival rate, even if performed by a junior trainee under the supervision of experienced surgeons in a nonspecialized hospital.